Lactobacillus plantarum SN13T Cells Improve Hepatic Dysfunction And Fecal Microbiota: A Randomized Pilot Study - Higashikawa, Fumiko; Danshiitsoodol, Narandalai; Kanno, Keishi; Ishida, Ryoko; Tazuma, Susumu; Sugiyama, Masanori (Archives of Clinical and Biomedical Research, 2020)
The liver dysfunction is a worldwide health problem. It has been suggested that an imbalance of gut microbiome is associated with a variety of diseases. The goal of the present clinical trial is to evaluate the effectiveness of Lactobacillus plantarum SN13T on hepatic function and fecal microbiota. This study enrolled 22 subjects, aged between 20 and 70 years, and who had any of the following conditions: 40<AST<100 U/L, 40<ALT<100 U/L, or 70<γ-GTP<210 U/L for males; 30<γ-GTP<90 U/L for females. The subjects were assigned to the live or heat-killed SN13T group. The intake period was 16 weeks followed by an 8-week follow-up period. Although no difference was observed between the two groups in the changes of AST, ALT, and γ-GTP, the subgroup analyses of subjects with over a certain level at baseline showed significant decreases in AST (-14.6 U/L, P=0.028) and ALT (-15.4 U/L, P=0.023) by SN13T, regardless of live or dead. The fecal microflora analysis showed an increase of Firmicutes and the decreases of Bacteroidetes and Fusobacteria in both groups. Bifidobacterium was increased only in the live SN13T group. In conclusion, Lactobacillus plantarum SN13T alters the composition of gut microbiota and improves liver function in subjects with mild liver dysfunction. This clinical trial was registered with University hospital Medical Information Network Clinical Trials Registry (UMIN-CTR) as UMIN000027440.